Entre dette et pardon ou la force liberatrice du recit - Henriques, Fernanda (B@belonline, 2021)
Being guided by the theme of forgiveness, this paper aims to articulate this problem with that of debt, in order to highlight the importance of storytelling in the process of liberating traumatic memories and memory’s ‘illnesses’ which, weighting on the present, ends up blocking the existence of individuals and peoples.